Ohmic heating curing of high content fly ash blended cement-based composites towards sustainable green construction materials used in severe cold region. (10th December 2020) - Tian, Weichen; Wang, Mingzhi; Liu, Yushi; Wang, Wei
Abstract: Fly ash (FA) is a common solid waste in those countries which depend much on coal resources. The recycling of FA as a partial substitute for cement concrete is significant to reduce the pressure of land source and environmental protection. In this work, ohmic heating (OH) curing method was presented to cure FA/cement mortar (FA-CM) samples under severely low temperature. Results showed that the FA-CM samples with 20 wt% FA cured by 2 days OH curing at −20 °C (FA20-OH) possessed comparable mechanical properties compared with the FA-CM sample without FA cured by 3 days room temperature (RT) curing (FA0-RT), indicating the significant role of OH curing in promoting strength growth under severely low temperature. Mercury intrusion porosimetry (MIP) characterization revealed that OH curing could refine the pore structure, and FA20-OH samples showed comparable total porosity compared with FA0-RT sample. Scanning electron microscopy (SEM) analysis indicated that OH curing could effectively densify the microstructure of FA-CM samples compared with RT curing. Moreover, a higher Ca(OH)2 content and larger mean chain length were observed in FA20-OH sample from thermogravimetric and differential scanning calorimetry (TG-DSC) analysis and 29 Si nuclear magnetic resonance (NMR) measurements to further clarify the positive regulation of OH curing on hydration product and its chemical structure. This study provided insights into the sustainable utilization of FA in construction materials used in severe cold region. Highlights: Ohmic heating curing method is developed for preparing FA-CM sample at ultralow temperature. Numerical and experimental analysis are conducted to determine the optimal CFs addition. FA10-OH and FA20-OH samples show comparable mechanical properties compared with FA0-RT sample. OH curing can compensate adverse effect caused by addition of FA and ultra-low temperature environment. FA-CM sample cured by OH curing is beneficial to both environmental protection and economic development in cold region.